PEMILIHAN SUPPLIER BAHAN BAKU UNTUK MEMINIMUMKAN BIAYA DENGAN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS DAN TAGUCHI LOSS FUNCTION - Helianty, Yanti; Anggraeni, Dyah (Teknik Industri Unikom, 2021)
To get the raw material for production, ussualy industri joint with supplier. Selection of the right supplier can help smooth the production process and make the company able to produce good quality products in accordance with the wishes of consumers so as to minimize losses caused by irregularities committed by the supplier. In this study the supplier selection process is based on the evaluation results of each supplier using the Analytical Hierarchy Process (AHP) and Taguchi Loss Function methods. AHP is used to determine the weight of each criterion, while the Taguchi Loss Function is used to calculate losses caused by deviations made by each supplier based on the weight of criteria that have been calculated using the AHP method. The criteria used in this study are price, quality, delivery, accuracy of the number of goods, and the payment system. The order of weight of each criterion is 0.3838 for quality criteria, 0.3009 for price criteria, 0.1408 for shipping criteria, 0.0874 for accuracy of quantity of goods and 0.0871 for payment system criteria. Whereas based on Taguchi Loss Function proposed priority for supplier of raw material based on the smallest loss value. Keywords: supplier selection, analytic hierarchy process, taguchi loss function